Halal Certification Standards for Chicken Slaughter in Traditional Markets - Sukardi, Didi; Hafizd, Jefik Zulfikar; Setiawan, Fajar Faturrachman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Slaughter is a halal condition that can be consumed by land animals. That is, these animals are not halal without the slaughter process. Some broiler chicken owners still ignore the slaughtering process in accordance with Islamic sharia. This research is a field research, namely research conducted at the location that is the object of research, namely Cigasong Traditional Market, Majalengka Regency. In this research the method used is interview.From the research, it was concluded that: slaughtering by Rabani Slaughter House in the Cigasong traditional market, which was slaughtered by Mr. Lalan's employees, the slaughtering process was in accordance with MUI Fatwa number 12 of 2009 concerning Halal Slaughter Certification Certification Standards. Regarding slaughtering of slaughtered chickens, the implementation of slaughtering carried out at Rabani Chicken slaughterhouses in the Cigasong traditional market has all been met with Halal Slaughtering Certification Standards. Then it is suggested: The owner of the slaughterhouse at the Cigasong traditional market must pay attention and ensure the slaughter, For the Majalengka Ulema Council should pay regular visits to the place of broiler sellers in the Cigasong traditional market against Halal Slaughter Certification Standards. Is it already running, implemented and implemented by every owner of the Chicken House.